Assessment of Stroke and Concomitant Cerebrovascular Disease with Heart Disease Requires Invasive Treatment: Analysis of 249 Consecutive Patients with Heart Disease - Kim, Myeong Jin; Song, Hyun; Oh, Se-yang; Choi, Jai Ho; Kim, Bum-soo; Kang, Joonkyu; Shin, Yong Sam (The Thoracic and Cardiovascular Surgeon, 2014)
Purpose The aim of this study was to analyze the relationships of cerebrovascular disease (CVD), heart problems, and stroke in patients who required an invasive cardiac procedure.Materials and Methods We enrolled 249 consecutive patients who required to or underwent invasive cardiac treatment and divided into a non-CVD group (n = 116) and a CVD group (n = 133). The latter group was divided into a coronary artery disease (CAD) group (n = 118) and a non-CAD group such as cardiac structural lesions (n = 15).Results No significant relationship with significant cerebrovascular stenosis was observed in either the CADs or non-CADs. The incidence of past stroke was significantly higher in the CVD group than that in the non-CVD group (12.8 vs. 3.4%; p = 0.017). Previous stroke event had increased odds of having significant cerebrovascular stenosis (odds ratio, 3.919, p = 0.006). In patients with both cardiac disease and the CVD, perioperative stroke was only one case (0.9%). The main source of stroke was cardiogenic in the immediate results and cerebrovascular lesions in the delayed results (1–12 months).Conclusion The risk of perioperative stroke was very low in combined cardiac disease and the CVD. However, for preventing ischemic stroke due to the predetected cerebrovascular lesions, precautionary efforts could be needed for patients undergoing an invasive cardiac procedure, and concomitant cerebrovascular lesions should be considered as main source of delayed ischemic stroke.
Keywords: coronary artery bypass graft; heart valve surgery; stroke; carotid arteries; atherosclerosis